Morphology of immature stages of Pyrearinus pumilus (Candèze, 1863 (Coleoptera: Elateridae: Pyrophorini): the click beetle responsible for the luminous canga caves in the state of Pará, Brazil - Rosa, Simone Policena; Mariano, Raone Dos Reis; Viviani, Vadim R.; Costa, Cleide (Zootaxa, 2020)
The Pyrearinus pumilus species group from South America includes luminescent click beetles (Agrypninae: Pyrophorini) associated with the phenomena of “luminescent termite mounds” and “luminous canga caves”. The latter was recently reported in the state of Pará, Brazil. This group includes six species based on the morphology of adults, of which two have immature stages already described. In this work we present the morphology and biological aspects of mature larva and pupa of Pyrearinus pumilus (Candèze, 1863), from the canga caves. Moreover, we provide a key and illustrations for identification of male adults and the known larvae. Our study shows that: (1) morphological characters of immatures support the close relationship of P. pumilus with their allies in the P. pumilus species group; (2) the traits of the known larvae of the P. pumilus species group are reliable for species identification.